The significance of the EEC's Generalized System of Preferences - Axel Borrmann (Intereconomics, 1986)
In 1986 the EEC's Generalized System of Preferences will be entering its 15th year. In line with the Community's decision for the granting of generalized tariff preferences for the period 1981–90 the time has come for an interim appraisal of the scheme with the aim of evaluating experiences gathered since the system was reformed at the end of 1980 and discussing modifications which may now seem expedient.
Keywords: 330; Trade Policy